No evidence for an involvement of alleles of polymorphisms in the serotonin 1Dβ and 7 receptor genes in obesity, underweight or anorexia nervosa - Hinney, Anke; Herrmann, H.; Löhr, T.; Rosenkranz, Klaus; Ziegler, A.; Lehmkuhl, Gerd; Poustka, Fritz; Schmidt, Martin H.; Mayer, H.; Siegfried, Walter; Remschmidt, Helmut; Hebebrand, Johannes (International journal of obesity and related metabolic disorders, 1999)
The serotonergic (5-hydroxytryptamine, 5-HT) system has been implicated in body weight regulation and in the etiology of anorexia nervosa (AN). Here we describe the screening of the known Phe-124-Cys polymorphism in the 5-HT1Dβ receptor gene and of the known Pro-279-Leu polymorphism in the 5-HT7 receptor gene. For association tests allele frequencies were compared between up to 393 extremely obese children and adolescents, 142 underweight students and 84 patients with AN. None of the association tests revealed nominal P-values below 0.3. We conclude that a major role of the investigated polymorphisms in body weight regulation or AN appears unlikely.